Ultra-wideband light and thin wave-absorbing organic silicon gasket and preparation method thereof

Through the method of high and low viscosity vinyl silicone oil compounding and wave absorbing powder ratio, ultra-wideband lightweight wave absorbing silicone gaskets were prepared, which solved the problem of narrow bandwidth of existing wave absorbing gaskets, and achieved a wide range of electromagnetic wave absorption bands and high-efficiency wave absorbing performance.

CN119752194AActive Publication Date: 2025-04-04RUITENG NEW MATERIAL MFG (SUZHOU) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510277235.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-04
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The effective absorption bandwidth of existing wave absorbing gaskets is relatively narrow, making it difficult to meet the demand for thin wave absorbing gaskets in modern electronic equipment.

Method used

By combining the combination of high and low viscosity vinyl silicone oil, ultra-wideband lightweight wave-absorbing silicone gaskets are prepared by combining soft magnetic, dielectric and carbonyl iron wave-absorbing powders.

Benefits of technology

When the wave-absorbing silicone gasket is thicker than 2mm or less, the effective absorption frequency band is widened, covering the 8-36.8GHz range, which significantly improves the wave-absorbing performance and is suitable for electronic devices in different frequency bands.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752194A_ABST
    Figure CN119752194A_ABST
Patent Text Reader

Abstract

The invention discloses an ultra-wideband light and thin wave-absorbing organic silicon gasket which is prepared from the following raw materials in percentage by mass: 20 to 40 weight percent of high-viscosity vinyl silicone oil, 1 to 5 weight percent of low-viscosity vinyl silicone oil, 2 to 20 weight percent of hydrogen-containing silicone oil, 0.2 weight percent of platinum catalyst, 5 to 15 weight percent of soft magnetic wave-absorbing powder, 15 to 25 weight percent of dielectric wave-absorbing powder and 25 to 40 weight percent of carbonyl iron wave-absorbing powder. The wave-absorbing organic silicon gasket is prepared by setting the raw materials in the proportion range, the principle is that a mode of compounding high-viscosity silicone oil and low-viscosity silicone oil is adopted, then the mode of reducing viscosity and wrapping the surface of the wave-absorbing powder is achieved, dispersion of the wave-absorbing powder is facilitated, meanwhile, the organic silicon gasket has high extension and good toughness, and the service life of the organic silicon gasket is prolonged. Through the matching, reasonable matching and synergistic effect of the three kinds of wave-absorbing powder, the electromagnetic wave absorbing frequency band of the wave-absorbing organic silicon gasket is widened, and the microwave frequency band can be covered under different thicknesses. The invention also discloses a preparation method of the wave-absorbing organic silicon gasket.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microwave-absorbing organic silicon gaskets, and in particular to an ultra-wideband, light and thin microwave-absorbing organic silicon gasket and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles and the communication industry, electronic equipment is being used more and more widely. Electromagnetic wave absorbing silicone materials are valued as functional materials that improve the electromagnetic environment and inhibit the mutual influence between electronic components. With the increasing integration of electronic components, higher requirements are placed on the performance of electromagnetic wave absorbing silicone gaskets, such as reducing their thickness to achieve thinner thickness in order to improve space utilization. For example, Chinese patent document CN117801533A discloses a high thermal conductivity and high insulation ultra-thin flexible absorbing composite material, which includes the following raw materials, by weight: 45-70 parts of modified absorbing powder, 40 parts of vinyl silicone oil, 5-10 parts of hydrogen-containing silicone oil, 50 parts of aluminum oxide powder, and 0.4 parts of catalyst. The modified absorbing powder, vinyl silicone oil, hydrogen-containing silicone oil, aluminum oxide powder and catalyst are mixed and stirred, and vacuum defoamed to obtain a thermal conductive absorbing mixed slurry; the thermal conductive absorbing mixed slurry is evenly coated on a carrier film by cast coating, and multi-step temperature gradient drying and curing is performed at 40-60°C, 65-135°C, 110-140°C, 60-90°C, and 25-50°C to obtain a 0.06-2mm high thermal conductivity and high insulation ultra-thin flexible absorbing composite gasket. For another example, Chinese patent document CN113249031B discloses a high thermal conductivity silicone absorber, which includes the following components by mass: 10-85 parts of resin, 41-120 parts of magnetic powder, 5-55 parts of thermal conductive filler, and 1.4-41 parts of auxiliary agent, wherein the resin is selected from one or more of polyalkyl silicone resin, polyaryl silicone resin and polyalkylaryl silicone resin; the molecular weight of the resin is 5000-120000; the thermal conductive filler is selected from one or more of aluminum oxide, aluminum oxide monohydrate, aluminum oxide dihydrate, iron oxide, zinc oxide, magnesium oxide, aluminum nitride, boron nitride, insulating carbon black, and graphene; the magnetic powder is selected from one or more of diamagnetic, paramagnetic, ferromagnetic, antiferromagnetic or ferrimagnetic powder, and the 1.4-41 parts of auxiliary agent include: 0.5-10 parts of cross-linking agent, 0.1-2 parts of coupling agent, 0.1-3 parts of antioxidant, 0. .1-3 parts of defoaming agent, 0.1-3 parts of wetting agent, 0.5-20 parts of PH regulator; obtain the following components by mass: 10-85 parts of resin, 41-120 parts of magnetic powder, 5-55 parts of thermal conductive filler, 1.4-41 parts of auxiliary agent; mix evenly at 2-5°C and vacuum conditions, add catalyst and solvent, mix evenly again to obtain slurry; S20: use the slurry for coating, the coating thickness is 0.15-3mm, and the absorbing sheet is obtained after drying. It can be seen that structures such as thin absorbing pads have appeared in the prior art, specifically absorbing pads less than or equal to 3mm, but the effective absorption bandwidth of the thin absorbing pads in the above technology is very narrow, which is difficult to meet the needs of modern electronic equipment for thin absorbing pads. Summary of the invention

[0003] To solve the above technical problems, the present invention provides an ultra-wideband, lightweight, and absorbing silicone gasket, which is formed by the following raw materials, in terms of mass percentage: 20wt%-40wt% of high-viscosity vinyl silicone oil, 1wt%-5wt% of low-viscosity vinyl silicone oil, 2wt%-20wt% of hydrogen-containing silicone oil, 0.2wt% of platinum catalyst, 5wt%-15wt% of soft magnetic absorbing powder, 15wt%-25wt% of dielectric absorbing powder, and 25wt%-40wt% of carbonyl iron absorbing powder. The absorbing silicone gasket is prepared by setting the raw materials in the above-mentioned proportion range. The principle is to use a compound method of high- and low-viscosity silicone oils to reduce viscosity and wrap the surface of the absorbing powder. While being beneficial to the dispersion of the absorbing powder, the silicone gasket has high ductility and good toughness. In addition, through the ratio of the above three absorbing powders, reasonable matching and synergistic effect, the electromagnetic wave absorption frequency band of the absorbing silicone gasket is broadened, and the microwave frequency band can be covered at different thicknesses, so that the absorbing silicone gasket can meet the needs of different frequency bands, overcoming the defect of the existing absorbing gaskets that the effective absorption bandwidth is very narrow, especially when the thickness is 2mm or less, especially when the thickness is 0.3-2mm, the effective absorption band (≤-10dB, electromagnetic wave absorption rate greater than 90%) of the absorbing silicone gasket prepared by the above-mentioned raw materials can cover at least 8-36.8GHz, which greatly improves the effective absorption band of the absorbing silicone gasket when it is thin, expands the scope of use, and is better than the 9.8-32.6 GHz coverage range of the absorbing gasket in the prior art.

[0004] In one embodiment, the following raw materials are used, in terms of mass percentage: 33.7wt% of high viscosity vinyl silicone oil, 3wt% of low viscosity vinyl silicone oil, 3.1wt% of hydrogenated silicone oil, 0.2wt% of platinum catalyst, 10wt% of soft magnetic absorbing powder, 20wt% of dielectric absorbing powder, and 30wt% of carbonyl iron absorbing powder. By further limiting the raw material range of the absorbing silicone gasket, the prepared absorbing silicone gasket has an effective absorption band (≤-10dB, electromagnetic wave absorption rate greater than 90%) of 5.5-40GHz (C, X, Ku, K, Ka bands) when the thickness is 2mm or less, especially 0.3-2mm, achieving the maximum coverage range; and, when the thickness of the absorbing silicone gasket is 0.4mm, the reflection loss is the lowest, and the strongest absorbing performance reaches -27dB, that is, the absorbing silicone gasket of the above ratio can still achieve good absorbing performance when it is very thin, which is far superior to the absorbing performance that the absorbing gasket in the prior art can only achieve when it is 2mm.

[0005] In one embodiment, the viscosity of the high viscosity vinyl silicone oil is 1000-10000 cs, the viscosity of the low viscosity vinyl silicone oil is 50-200 cs, and the viscosity of the hydrogen-containing silicone oil is 20-200 cs.

[0006] In one embodiment, the high viscosity vinyl silicone oil is at least one of terminal vinyl silicone oil, side vinyl silicone oil and terminal side vinyl silicone oil; the low viscosity vinyl silicone oil is at least one of terminal vinyl silicone oil, side vinyl silicone oil and terminal side vinyl silicone oil; the hydrogen-containing silicone oil is at least one of terminal hydrogen-containing silicone oil and side hydrogen-containing silicone oil; and the platinum catalyst is a Karstedt catalyst.

[0007] In one embodiment, the sum of the mass percentages of the soft magnetic absorbing powder, the dielectric absorbing powder and the carbonyl iron absorbing powder is 50wt%-70wt%. The best effect is achieved by controlling the total ratio of the three absorbing powders to be 50-70wt%.

[0008] In one embodiment, the soft magnetic absorbing powder is at least one of iron-based alloy powders such as sendust, iron-nickel, and iron-cobalt alloy and / or ferrite; the dielectric absorbing powder is at least one of barium titanate, silicon carbide, silicon nitride, boron nitride, and iron nitride.

[0009] In one embodiment, the particle size of the soft magnetic absorbing powder is 50-200 μm; the particle size of the dielectric absorbing powder is 3-50 μm; and the particle size of the carbonyl iron absorbing powder is 3-50 μm.

[0010] In one embodiment, the soft magnetic absorbing powder, the dielectric absorbing powder and the carbonyl iron absorbing powder are in the shape of one or more of sphere, rhombus, dendrite, flake and needle.

[0011] The invention also discloses a method for preparing an ultra-wideband, light and thin wave-absorbing organic silicon gasket, which comprises the following steps.

[0012] (1) Stirring: The high-viscosity vinyl silicone oil, the low-viscosity vinyl silicone oil, the hydrogen-containing silicone oil and the platinum catalyst are uniformly stirred under vacuum; then the soft magnetic absorbing powder, the dielectric absorbing powder and the carbonyl iron absorbing powder are added, first stirred until there is no powder, and then vacuum stirred to obtain a mixed slurry of silicone oil and absorbing powder.

[0013] (2) Calendering: Place the mixed slurry on a release paper, cover the upper layer with a release film, and use a calendering machine for calendering; then, vulcanize in a high-temperature oven to form a semi-finished absorbing silicone gasket.

[0014] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket.

[0015] Furthermore, in step (1), the vacuum stirring time is 1-3 minutes; in step (2), the thickness of the release paper is 0.2-0.5 mm, the thickness of the centrifugal membrane is 20 μm-100 μm, the length of the high-temperature drying tunnel is 8-12 m, the conveying speed is 0.5-1 m / min, and the temperature of the high-temperature drying tunnel is 80°C-120°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the specific implementation modes of the present invention, the following briefly introduces the drawings required for use in the specific implementation modes. Obviously, the drawings described below are some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 It is a reflection loss diagram of the wave-absorbing silicone gasket of Example 1 of the present invention.

[0018] Figure 2 It is a reflection loss diagram of the wave-absorbing silicone gasket of Example 2 of the present invention.

[0019] Figure 3 It is a reflection loss diagram of the absorbing silicone gasket of Example 3 of the present invention.

[0020] Figure 4 It is a reflection loss diagram of the wave-absorbing silicone gasket of Example 4 of the present invention.

[0021] Figure 5 It is a reflection loss diagram of the wave-absorbing silicone gasket of Example 5 of the present invention.

[0022] Figure 6 It is a reflection loss diagram of the wave-absorbing silicone gasket of Example 6 of the present invention.

[0023] Figure 7 It is a reflection loss diagram of the wave-absorbing silicone gasket of Example 7 of the present invention.

[0024] Figure 8 It is a reflection loss diagram of the wave-absorbing silicone gasket of Example 8 of the present invention.

[0025] Fig. 9 It is a reflection loss diagram of the wave absorbing pad of comparative example 1 of the present invention. DETAILED DESCRIPTION

[0026] The following is a clear and complete description of the content of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The embodiments in the present invention and other embodiments obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention.

[0027] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0028] In the following embodiments, the manufacturer of high-viscosity vinyl silicone oil, low-viscosity vinyl silicone oil and hydrogen-containing silicone oil is Ningbo Runhe High-tech Materials Technology Co., Ltd.; the platinum catalyst is Karstedt catalyst, manufactured by Wacker (China) Technology Co., Ltd.; the manufacturer of carbonyl iron (wherein C < 0.75, O < 0.50, N < 0.75) is Jiangsu Tianyi Ultrafine Metal Powder Co., Ltd.; the manufacturer of sendustine is Taicang Xianghui Electronic Materials Co., Ltd.; the manufacturer of barium titanate is Tianjin Jersey Mineral Processing Co., Ltd.; the manufacturer of silicon carbide is Shandong Jinmeng New Materials Co., Ltd. Example 1

[0029] (1) Stirring: 33.7wt% of 5000cs vinyl-terminated silicone oil, 3wt% of 100cs vinyl-terminated silicone oil, 3.1wt% of 100cs hydrogen-terminated silicone oil and 0.2% platinum catalyst were placed in a vacuum homogenizer and stirred evenly, wherein the stirring speed was 600 r / min, the stirring time was 2 min, and the vacuum degree was -0.08MPa; then 10wt% of 100μm-sized flake iron silicon aluminum, 20wt% of 10μm-sized barium titanate and 30wt% of 10μm-sized hydroxy iron were added, first stirred until there was no powder, and then vacuum stirred evenly, wherein the stirring speed was 800 r / min, the stirring time was 3 min, and the vacuum degree was -0.08mMPa, to obtain a mixed slurry of silicone oil and absorbing powder.

[0030] (2) Calendering: The mixed slurry is placed on a 0.2 mm thick release paper, and the upper layer is covered with a 20 μm thick release film, and calendered by a calendering machine; then, the mixed slurry is vulcanized in an 8 m long high-temperature drying tunnel to form a semi-finished absorbing silicone gasket, wherein the conveying speed is 0.5 m / min and the temperature is 100°C; wherein the thickness of the semi-finished absorbing silicone gasket is 2 mm.

[0031] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket. Example 2

[0032] (1) Stirring: 19.8wt% of terminal vinyl silicone oil with a viscosity of 1000cs, 1wt% of side vinyl silicone oil with a viscosity of 50cs, 19wt% of side hydrogen silicone oil with a viscosity of 20cs and 0.2% of platinum catalyst are placed in a vacuum homogenizer and stirred evenly, wherein the stirring speed is 800 r / min, the stirring time is 2 min, and the vacuum degree is -0.09MPa; then, 10wt% of iron-nickel alloy with a particle size of 100μm (iron-nickel weight ratio is 1:1, produced by Shijia Weier Technology Co., Ltd.), 20wt% of silicon carbide with a particle size of 10μm and 30wt% of hydroxy iron with a particle size of 10μm are added, first stirred until there is no powder, and then vacuum stirred evenly, wherein the stirring speed is 600r / min, the stirring time is 4min, and the vacuum degree is -0.08mMPa, to obtain a mixed slurry of silicone oil and absorbing powder.

[0033] (2) Calendering: The mixed slurry is placed on a 0.5 mm thick release paper, and the upper layer is covered with a 50 μm thick release film, and calendered by a calendering machine; then, the mixed slurry is vulcanized in a 12 m long high-temperature drying tunnel to form a semi-finished absorbing silicone gasket, wherein the conveying speed is 1 m / min and the temperature is 120°C; wherein the thickness of the semi-finished absorbing silicone gasket is 2 mm.

[0034] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket. Example 3

[0035] (1) Stirring: 34.8wt% of terminal vinyl silicone oil with a viscosity of 10000cs, 3wt% of terminal side vinyl silicone oil with a viscosity of 200cs, 2wt% of terminal hydrogen silicone oil with a viscosity of 200cs and 0.2% of platinum catalyst were placed in a vacuum homogenizer and stirred evenly, wherein the stirring speed was 600 r / min, the stirring time was 3 min, and the vacuum degree was -0.09MPa; then 10wt% of iron-cobalt alloy with a particle size of 100μm (iron-cobalt weight ratio of 1:1, produced by Hebei Junchen Metal Products Co., Ltd.), 20wt% of silicon nitride with a particle size of 10μm (produced by Shanghai Yaotian New Materials Technology Co., Ltd.) and 30wt% of hydroxy iron with a particle size of 10μm were added, first stirred until there was no powder, and then vacuum stirred evenly, wherein the stirring speed was 800 r / min, the stirring time was 2 min, and the vacuum degree was -0.09mMPa, to obtain a mixed slurry of silicone oil and absorbing powder.

[0036] (2) Calendering: The mixed slurry is placed on a 0.2 mm thick release paper, and the upper layer is covered with a 100 μm thick release film, and calendered by a calendering machine; then, the mixed slurry is vulcanized in an 8 m long high-temperature drying tunnel to form a semi-finished absorbing silicone gasket, wherein the conveying speed is 0.5 m / min and the temperature is 120°C; wherein the thickness of the semi-finished absorbing silicone gasket is 2 mm.

[0037] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket. Example 4

[0038] (1) Stirring: 39.8 wt% of side vinyl silicone oil with a viscosity of 5000 cs, 5 wt% of terminal vinyl silicone oil with a viscosity of 100 cs and 5 wt% of terminal hydrogen silicone oil with a viscosity of 100 cs were placed in a vacuum homogenizer and stirred evenly, wherein the stirring speed was 800 r / min, the stirring time was 1 min, and the vacuum degree was -0.08 MPa; then 5 wt% of ferroferric oxide with a particle size of 100 μm (Jiangxi Yuean New Materials Co., Ltd.), 20 wt% of boron nitride with a particle size of 10 μm (produced by Yingkou Liaobin Fine Chemical Co., Ltd.) and 25 wt% of hydroxy iron with a particle size of 10 μm were added, first stirred until there was no powder, and then vacuum stirred evenly, wherein the stirring speed was 600 r / min, the stirring time was 3 min, and the vacuum degree was -0.08 mMPa, to obtain a mixed slurry of silicone oil and absorbing powder.

[0039] (2) Calendering: The mixed slurry is placed on a 0.5 mm thick release paper, and the upper layer is covered with a 20 μm thick release film, and calendered by a calendering machine; then, the mixed slurry is vulcanized in a 12 m long high-temperature drying tunnel to form a semi-finished absorbing silicone gasket, wherein the conveying speed is 1 m / min and the temperature is 80°C; wherein the thickness of the semi-finished absorbing silicone gasket is 2 mm.

[0040] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket. Example 5

[0041] (1) Stirring: 24.8wt% of end-side vinyl silicone oil with a viscosity of 5000cs, 3wt% of end-side vinyl silicone oil with a viscosity of 100cs, 1wt% of end-hydrogen silicone oil with a viscosity of 100cs, 1wt% of side vinyl silicone oil with a viscosity of 100cs and 0.2% of platinum catalyst were placed in a vacuum homogenizer and stirred evenly, wherein the stirring speed was 600 r / min, the stirring time was 2min, and the vacuum degree was -0.09MPa; then 10wt% of sendustine with a particle size of 100μm, 5wt% of iron-nickel alloy with a particle size of 100μm (iron-nickel weight ratio of 1:1, produced by Hebei Junchen Metal Products Co., Ltd.), 15wt% of barium titanate with a particle size of 10μm and 40wt% of hydroxy iron with a particle size of 10μm were added, first stirred until there was no powder, and then vacuum stirred evenly, wherein the stirring speed was 800 r / min, the stirring time was 1 min, the vacuum degree was -0.09 mMPa, and a mixed slurry of silicone oil and absorbing powder was obtained.

[0042] (2) Calendering: The mixed slurry is placed on a 0.2 mm thick release paper, and the upper layer is covered with a 50 μm thick release film, and calendered by a calendering machine; then, the mixed slurry is vulcanized in an 8 m long high-temperature drying tunnel to form a semi-finished absorbing silicone gasket, wherein the conveying speed is 0.5 m / min and the temperature is 100°C; wherein the thickness of the semi-finished absorbing silicone gasket is 2 mm.

[0043] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket. Example 6

[0044] (1) Stirring: 10 wt% of side vinyl silicone oil with a viscosity of 5000 cs, 16.8 wt% of terminal vinyl silicone oil with a viscosity of 5000 cs, 3 wt% of terminal vinyl silicone oil with a viscosity of 100 cs, 10 wt% of terminal hydrogen silicone oil with a viscosity of 100 cs and 0.2% of platinum catalyst were placed in a vacuum homogenizer and stirred evenly, wherein the stirring speed was 800 r / min, the stirring time was 1 min, and the vacuum degree was -0.08 MPa; then 10 wt% of iron silicon aluminum with a particle size of 100 μm, 15 wt% of barium titanate with a particle size of 30 μm, 5 wt% of silicon carbide with a particle size of 30 μm and 30 wt% of hydroxy iron with a particle size of 30 μm were added, first stirred until there was no powder, and then vacuum stirred evenly, wherein the stirring speed was 600 r / min, the stirring time was 3 min, and the vacuum degree was -0.09 mMPa, to obtain a mixed slurry of silicone oil and absorbing powder.

[0045] (2) Calendering: The mixed slurry is placed on a 0.5 mm thick release paper, and the upper layer is covered with a 100 μm thick release film, and calendered by a calendering machine; then, the mixed slurry is vulcanized in a 12 m long high-temperature drying tunnel to form a semi-finished absorbing silicone gasket, wherein the conveying speed is 1 m / min and the temperature is 120°C; wherein the thickness of the semi-finished absorbing silicone gasket is 2 mm.

[0046] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket. Example 7

[0047] (1) Stirring: 21.8wt% of 5000cs vinyl-terminated silicone oil, 1wt% of 100cs vinyl-terminated silicone oil, 2wt% of 100cs vinyl-side silicone oil, 15wt% of 100cs hydrogen-terminated silicone oil and 0.2% platinum catalyst were placed in a vacuum homogenizer and stirred evenly, wherein the stirring speed was 600 r / min, the stirring time was 1 min, and the vacuum degree was -0.09MPa; then 10wt% of 200μm-sized flake iron silicon aluminum, 20wt% of 50μm-sized barium titanate and 30wt% of 50μm-sized hydroxy iron were added, first stirred until there was no powder, and then vacuum stirred evenly, wherein the stirring speed was 800 r / min, the stirring time was 2 min, and the vacuum degree was -0.09mMPa, to obtain a mixed slurry of silicone oil and absorbing powder.

[0048] (2) Calendering: The mixed slurry is placed on a 0.2 mm thick release paper, and the upper layer is covered with a 20 μm thick release film, and calendered by a calendering machine; then, the mixed slurry is vulcanized in an 8 m long high-temperature drying tunnel to form a semi-finished absorbing silicone gasket, wherein the conveying speed is 0.5 m / min and the temperature is 80°C; wherein the thickness of the semi-finished absorbing silicone gasket is 2 mm.

[0049] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket. Example 8

[0050] (1) Stirring: 28.7wt% of terminal vinyl silicone oil with a viscosity of 5000cs, 3wt% of side vinyl silicone oil with a viscosity of 100cs, 3.1wt% of terminal hydrogen silicone oil with a viscosity of 100cs and 0.2% of platinum catalyst are placed in a vacuum homogenizer and stirred evenly, wherein the stirring speed is 800 r / min, the stirring time is 1 min, and the vacuum degree is -0.08MPa; then, 10wt% of flaky iron silicon aluminum with a particle size of 50μm, 25wt% of barium titanate with a particle size of 3μm and 30wt% of hydroxy iron with a particle size of 3μm are added, first stirred until there is no powder, and then vacuum stirred evenly, wherein the stirring speed is 600 r / min, the stirring time is 3min, and the vacuum degree is -0.08mMPa, to obtain a mixed slurry of silicone oil and absorbing powder.

[0051] (2) Calendering: The mixed slurry is placed on a 0.5 mm thick release paper, and the upper layer is covered with a 50 μm thick release film, and calendered by a calendering machine; then, the mixed slurry is vulcanized in a 12 m long high-temperature drying tunnel to form a semi-finished absorbing silicone gasket, wherein the conveying speed is 0.5 m / min and the temperature is 100 ° C; wherein the thickness of the semi-finished absorbing silicone gasket is 2 mm.

[0052] (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket. Comparative Example 1

[0053] S10: Obtain the following components in parts by mass: 60 parts of resin (molecular weight 12000), 100 parts of carbonyl iron powder, 10 parts of graphene, 1 part of cross-linking agent, 0.8 parts of coupling agent, 1.2 parts of antioxidant, 0.3 parts of defoaming agent, 0.5 parts of wetting agent, and 5 parts of pH adjusting agent; mix them evenly at 2°C and vacuum conditions; after stirring evenly, add a catalyst, add a solvent to adjust the viscosity, and control the viscosity at 1000mPa·s, and stir evenly again to obtain the slurry; wherein the resin is selected from polyalkyl silicone resin, polyaryl silicone resin and polyalkylaryl silicone resin; the cross-linking agent is glycidyl ether; the coupling agent is aminosilane coupling agent; the antioxidant is bleaching agent; the defoaming agent is a silicone defoaming agent; the wetting agent is a silicone wetting agent; the pH adjusting agent is 2-amino-2-methyl-1-propanol; and the solvent is a benzene solvent.

[0054] S20: Forming an absorbing gasket by subjecting the slurry to the calendering and cutting process of Example 1. Test Case

[0055] The 2 mm thick absorbing silicone gaskets and absorbing gaskets obtained in Examples 1-8 and Comparative Example 1 were tested, and the specific test items were: effective absorption band coverage test and stretching test.

[0056] 1. Effective absorption band coverage experiment.

[0057] According to the National Standard of the People's Republic of China GB / T32596-2016-General Specification for Electromagnetic Shielding Absorbers, the absorbing performance of the absorbers was tested using the Keysight Technologies (China) Co., Ltd. network analyzer E5080B (100kHz-44GHz) and transmission lines. The details are as follows.

[0058] 1. Prepare test samples.

[0059] 1.1 Coaxial transmission line test The test sample is a concentric ring specimen.

[0060] The outer diameter is 6.95-7.00mm, the inner diameter is 3.05-3.10mm, and the concentricity deviation is less than 0.1mm.

[0061] 1.2 The waveguide transmission line sample is a rectangular specimen.

[0062] The length is ±0.05 mm of the basic width of the inner section of the waveguide, and the height is ±0.05 mm of the basic height of the inner section of the waveguide.

[0063] 2. Use SOLT to calibrate the vector network analyzer.

[0064] 3. Place the absorber to be tested in the test fixture for testing. After placement, the sample surface should be perpendicular to the incident direction of the electromagnetic wave and should not be bent or tilted. The S parameters are obtained by testing.

[0065] 4. Process and plot the data obtained from the test. Figure 1-9 shown.

[0066] According to the above Figure 1-9 The results were analyzed by Figure 1-Figure 9 The results are shown in Table 1. Figure 1-9It can be seen from the results in Table 1 that when the thickness of the absorbing silicone gasket obtained in Examples 1-8 is less than or equal to 2 mm, the effective absorption band (≤-10dB, electromagnetic wave absorption rate greater than 90%) covers at least 8-36.8 GHz, which is greater than the effective absorption band (≤-10dB, electromagnetic wave absorption rate greater than 90%) of 9.8-32.6 GHz of the absorbing gasket in the prior art when the thickness is less than or equal to 2 mm; in other words, the absorption bandwidth of the absorbing silicone gasket obtained in Examples 1-8 is at least 28.8 GHz when the thickness is less than or equal to 2 mm, which is greater than the absorption bandwidth of 22.8 GHz of the absorbing gasket in the prior art when the thickness is less than or equal to 2 mm. Among them, when the thickness of the absorbing silicone gasket in Example 1 is less than or equal to 2 mm, the effective absorption band (≤-10dB, electromagnetic wave absorption rate greater than 90%) covers 5.5-40.0 GHz, and the absorption bandwidth is 34.5 GHz, which is far superior to the absorbing gasket in the prior art. Moreover, the maximum absorption intensity of the absorbing silicone gaskets of Examples 1-8 when less than or equal to 2 mm is greater than that of the prior art, especially the maximum absorption intensity of the absorbing gaskets of the prior art is 2 mm, while the maximum absorption intensity of Examples 1-8 is less than 2 mm, indicating that the absorption intensity of the absorbing silicone gasket of the present application is better than the absorption intensity of the absorbing gasket of the same thickness in the prior art when the thickness is thin, and can even reach the absorption intensity of the thicker absorbing gasket in the prior art, and especially the absorbing silicone gasket of Example 1 has a maximum absorption intensity of -27 dB when it is 0.4 mm thick, which can achieve a greater absorption intensity with a thinner thickness, and is more suitable for applications with smaller spaces. In summary, the absorbing silicone gasket of the present application can achieve the absorption bandwidth and intensity of the absorbing gaskets of the prior art when they are thicker, and is even better, and is suitable for small space applications.

[0067] Table 1 Effective absorption frequency band (GHz) Absorption bandwidth (GHz) (RL<-10dB) Absorption intensity (dB) Center frequency Example 1 5.5~40.0GHz 34.5 -27 (0.4mm) 36 Example 2 5.5~39.8GHz 34.3 -42.8 (0.8mm) 18.6 Example 3 7.4~38.7GHz 31.3 -25.8 (1mm) 13.4 Example 4 10.6~40.0GH 29.4 -25.5(1.1mm) 24 Example 5 6.2~40GHz 33.8 -31.1(0.7mm) 21.1 Example 6 5.6~36.8GHz 31.2 -30.8(1.2mm) 11.5 Example 7 8~36.8GHz 28.8 -39.6 (1.9mm) 10.2 Example 8 6.0 ~40.0GHz 34 -29.0 (1.0 mm) 14 Comparative Example 1 9.8~32.6GHz 22.8 -24.8 (2mm) 14.8

[0068] 2. Tensile test.

[0069] According to the National Standard of the People's Republic of China GB / T528-2009 / ISO37:2005 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, the tensile properties of the gasket are tested. The test method is as follows.

[0070] 1. Preparation of test samples.

[0071] Prepare no less than 3 dumbbell-shaped test samples of appropriate sizes according to national standards.

[0072] 2. Test samples.

[0073] Clamp the test piece symmetrically on the upper and lower clamps of the tensile testing machine so that the tensile force is evenly distributed on the cross section. Set the moving speed according to the standard, start the testing machine, and monitor the changes in the length and force of the specimen.

[0074] 3. Calculate the elongation at break and tensile strength based on the test results and draw a chart. See Table 2 for details.

[0075] Table 2 Tensile Strength Elongation at break Example 1 0.209MPa 127% Example 2 0.102MPa 39% Example 3 0.156MPa 38% Example 4 0.188MPa 81% Example 5 0.110MPa 93% Example 6 0.132MPa 100% Example 7 0.110MPa 74% Example 8 0.123MPa 65% Comparative Example 1 0.080MPa 20%

[0076] It can be seen from the data in Table 2 that the tensile strength and elongation at break of the absorbing silicone gaskets of Examples 1-8 are better than those of the absorbing silicone gaskets of the prior art, indicating that the absorbing silicone gaskets of the present application are more focused on application and achieve a longer service life.

[0077] It should be noted that, in the above embodiments, all powders are spherical except for the confirmed shape. In the reflection loss diagram, the thickness of the absorbing silicone gasket decreases from left to right.

[0078] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An ultra-wideband, light and thin microwave-absorbing silicone gasket, characterized in that: The invention is composed of the following raw materials, in terms of mass percentage: 20wt%-40wt% of high-viscosity vinyl silicone oil, 1wt%-5wt% of low-viscosity vinyl silicone oil, 2wt%-20wt% of hydrogen-containing silicone oil, 0.2wt% of platinum catalyst, 5wt%-15wt% of soft magnetic absorbing powder, 15wt%-25wt% of dielectric absorbing powder, and 25wt%-40wt% of carbonyl iron absorbing powder.

2. The ultra-wideband thin and light-weight organic silicon gasket according to claim 1, characterized in that: Calculated by mass percentage, it is composed of the following raw materials: 33.7wt% of high viscosity vinyl silicone oil, 3wt% of low viscosity vinyl silicone oil, 3.1wt% of hydrogen-containing silicone oil, 0.2wt% of platinum catalyst, 10wt% of soft magnetic absorbing powder, 20wt% of dielectric absorbing powder, and 30wt% of carbonyl iron absorbing powder.

3. The ultra-wideband thin and light-weight organic silicon gasket according to claim 1 or 2, characterized in that: The viscosity of the high-viscosity vinyl silicone oil is 1000-10000 cs, the viscosity of the low-viscosity vinyl silicone oil is 50-200 cs, and the viscosity of the hydrogen-containing silicone oil is 20-200 cs.

4. The ultra-wideband thin and light-weight organic silicon gasket according to claim 1 or 2, characterized in that: The high-viscosity vinyl silicone oil is at least one of terminal vinyl silicone oil, side vinyl silicone oil and terminal side vinyl silicone oil; the low-viscosity vinyl silicone oil is at least one of terminal vinyl silicone oil, side vinyl silicone oil and terminal side vinyl silicone oil; the hydrogen-containing silicone oil is at least one of terminal hydrogen-containing silicone oil and side hydrogen-containing silicone oil; the platinum catalyst is a Karstedt catalyst.

5. The ultra-wideband thin and light-weight organic silicon gasket according to claim 1 or 2, characterized in that: The sum of the mass percentages of the soft magnetic absorbing powder, the dielectric absorbing powder and the carbonyl iron absorbing powder is 50wt%-70wt%.

6. The ultra-wideband thin and light-weight organic silicon gasket according to claim 1 or 2, characterized in that: The soft magnetic absorbing powder is at least one of iron-based alloy powders such as sendust, iron-nickel, iron-cobalt and / or ferrite; the dielectric absorbing powder is at least one of barium titanate, silicon carbide, silicon nitride, boron nitride and iron nitride.

7. The ultra-wideband thin and light microwave-absorbing silicone gasket according to claim 1 or 2, characterized in that: The particle size of the soft magnetic absorbing powder is 50-200 μm; the particle size of the dielectric absorbing powder is 3-50 μm; and the particle size of the carbonyl iron absorbing powder is 3-50 μm.

8. The ultra-wideband thin and light-weight organic silicon gasket according to claim 1 or 2, characterized in that: The soft magnetic absorbing powder, the dielectric absorbing powder and the carbonyl iron absorbing powder have a shape of one or more of sphere, rhombus, dendrite, sheet and needle.

9. A method for preparing an ultra-wideband thin and light-weight microwave-absorbing silicone gasket, characterized in that: The following steps are involved: (1) Stirring: The high-viscosity vinyl silicone oil, the low-viscosity vinyl silicone oil, the hydrogen-containing silicone oil and the platinum catalyst are uniformly stirred in a vacuum; then the soft magnetic absorbing powder, the dielectric absorbing powder and the carbonyl iron absorbing powder are added, first stirred until there is no powder, and then vacuum stirred to obtain a mixed slurry of silicone oil and absorbing powder; (2) Calendering: Place the mixed slurry on a release paper, cover the release film on the top, and use a calendering machine for calendering; then, vulcanize the semi-finished microwave-absorbing silicone gasket through a high-temperature drying oven; (3) Cutting: Cut the semi-finished microwave-absorbing silicone gasket after vulcanization to obtain a finished microwave-absorbing silicone gasket.

10. The method for preparing the ultra-wideband thin and light-weight microwave-absorbing silicone gasket according to claim 9, characterized in that: In step (1), the vacuum stirring time is 1-3 minutes; in step (2), the thickness of the release paper is 0.2-0.5 mm, the thickness of the centrifugal membrane is 20-100 μm, the length of the high-temperature drying tunnel is 8-12 m, the conveying speed is 0.5-1 m / min, and the temperature of the high-temperature drying tunnel is 80-120°C.

Citation Information

Patent Citations

  • A high thermal conductivity silicone microwave absorber and its preparation method

    CN113249031B

  • High-thermal-conductivity high-insulation ultrathin flexible wave-absorbing composite material and preparation method thereof

    CN117801533A

  • Heat-conducting wave-absorbing gasket and preparation method thereof

    CN114231039A

  • Composite material gasket, preparation method and application thereof, and electronic device

    CN114891353A

  • Insulating, heat-conducting and wave-absorbing composite powder as well as preparation method and application thereof

    CN116102791A